Low temperature techniques for natural gas purification and LNG production: An energy and exergy analysis. (15th October 2016) - Baccanelli, Margaret; Langé, Stefano; Rocco, Matteo V.; Pellegrini, Laura A.; Colombo, Emanuela
Highlights: Low-temperature processes for of high CO2 content natural gas have been modelled. Energy and exergy analyses have been performed. The Dual Pressure distillation scheme has the best thermodynamic performances. There is a synergy between cryogenic natural gas purification and LNG production. Abstract: Due to the rapid increase of the World's primary energy demand of the last decades, low-temperature processes for the purification of natural gas streams with high carbon dioxide content has gained interest, since they allow to make profitable exploitation of low-quality gas reserves. Low temperature purification processes allow the direct production of a methane stream at high purity and at low-temperature, suitable conditions for the direct synergistic integration with natural gas cryogenic liquefaction processes, while CO2 is obtained in liquid phase and under pressure. In this way, it can be pumped for transportation, avoiding significant compression costs as for classical CO2 capture units (where carbon dioxide is discharged in gas phase and at atmospheric pressure), and further uses such as Enhanced Oil Recovery (EOR) or underground storage. In this paper, the three most common natural gas low-temperature purification techniques have been modelled and their performances have been evaluated through energy and exergy analyses. Specifically, the dual pressure low-temperature distillation process, the anti-sublimation process and a hybrid configuration have been considered. It is found that the dual pressure low-temperature distillation scheme reach the highest thermodynamic performances, resulting in the best values of exergy efficiency and equivalent methane requirements with respect to the other configurations. This is mainly due to the distributed temperature profile along a distillation column, resulting in a less irreversible heat exchanging process.